Characteristics of Consecutive Interpreting Strategies Employed by Multicultural Student Interpreters and Early Professional Interpreters - Achmad Suyono; Maulidiyah, Fitrotul; Hariyanto, Sugeng; Nadia Hanayeen (Jurnal Ijtihad, 2024)
Interpreters need to employ appropriate interpreting strategies to prevent information overload. The skills to employ such strategies may be associated to their experience. The current study investigates interpreting strategies employed by inexperienced novice interpreters (students) and more experienced interpreters (early professionals). The objective of this study is to make a comparison between interpreting strategies adopted by novice interpreters and those by early professional interpreters. The participants of the study were twenty students taking consecutive interpreting course and nine early professional interpreters. The data, gathered from video recordings of consecutive interpreting tasks, were analyzed to identify the strategies employed by the interpreters. The findings show that there are four strategies employed by the novice interpreters and six by the early professionals. The four strategies by the novice interpreters are skipping, word for word translation, guessing, and reproduction. The six strategies by the early professional interpreters are stalling, reproduction, word for word interpretation, inferencing, approximation, and taking advantage of cohesive markers. This shows that the early professional interpreters have wider repertoire of interpreting strategies compared to their novice counterparts. The limited number of strategies employed by the novice interpreters may be caused by their limited listening capacity, limited vocabulary, and their note taking skills. This implies that the consecutive interpreting course needs to be offered for students having passed courses on basic language skills. The second implication is that the consecutive interpreting materials need to include materials on active listening, chunking, and note taking.